The transition of Public Adult Learning Centres (PALCs) to Community Education and Training Colleges (CETCs): Perspectives and experiences of a selection of management and lecturer staff in the greater Cape Town area - Mginywa, Nondumiso (School of Education, 2021)
In 2013, the Department of Higher Education established a new institutional form for the provision of adult education, the Community Education and Training Colleges (CETCs). The growing number of unemployed youths that are not in learning institutions as well as the limited opportunities provided by the pre-existing Public Adult Learning Centres (PALCs), set the context for the transitioning of PALCs into CETCs. This transition marks one of the biggest changes to the adult education landscape historically in South Africa but has thus far been the subject of limited research. This study focuses on the experiences and perspectives of a selection of role players of this transition, in particular, those of managers and lecturers within the greater Cape Town area. The study was situated within an interpretive research paradigm with its emphasis on experience and interpretation and adopted a case study approach. A range of documents provided background data, while the main body of data was collected via semi-structured interviews. Adopting a thematic approach, the analysis focuses on how the policy changes have affected governance, experiences of the new institutional context and perspectives on lecturer qualifications. A further focus is on the views of key role players on the purposes of the CETCs and locating these within different theoretical traditions. The analysis also explored views on the professionalization of adult education and training, and how these compare with broader conceptual approaches to professionalisation in the literature. The study concludes that centralization of governance has had negative consequences for the management and lecturers represented in the sample and seems to be at odds with the ethos of institutional autonomy that usually characterises higher education. At the same time, the transition has presented opportunities for the CETCs to collaborate with different organisations to create skills development opportunities for their constituencies, especially for the increasing number of younger students in the CLCs. The evidence also suggests that while policies talk of CETCs continuing South Africa's historical traditions of transformative adult education, the respondents hold a more humanist view of their purpose, combined with some elements of a human capital approach. Respondents' views on professionalisation were largely instrumental, relating perhaps to continuing poor conditions of employment and scarcity of resources. However, the passion for and deep commitment of lecturers to their work is notable and seems to offer a basis not only for a future occupational identity, but also possibly for a more transformative education to take root in the CLCs.